1996
DOI: 10.1123/pes.8.2.143
|View full text |Cite
|
Sign up to set email alerts
|

Isokinetic Peak Torque in Young Wrestlers

Abstract: The purpose of the present study was to examine age-related changes in isokinetic leg flexion and extension peak torque (PT), PT/body weight (PT/ BW), and F*T/fat-free weight (PT/FFW) in young wrestlers. Male wrestlers (A= 108; age M ± SD = 11.3 + 1.5 years) volunteered to be measured for peak torque at 30, 180, and 300° • s'. In addition, underwater weighing was performed to determine body composition characteristics. The sample was divided into six age groups (8.1-8.9, n = 10; 9.0-9.9, n= 11; 10.0-10.9, n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 24 publications
3
7
0
1
Order By: Relevance
“…However, in the present study no signi®cant dierences in isometric MVC force of plantar¯exor muscles relative to body mass were found among the pre-and post-pubertal boys and men. These ®ndings were consistent with several other studies (Seger and Thorstensson 1994;Housh et al 1996) the results of which have indicated that age-related increases in voluntary muscle strength are not accounted for by changes in body mass. The studies which have used anthropometric indices (Davies et al 1983) or ultrasonic techniques (Ikai and Fukunaga 1968) have reported that isometric strength expressed per unit of muscle crosssectional area (CSA) of plantar¯exor and elbow¯exor muscles would appear to remain unchanged throughout adolescence and early adulthood.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, in the present study no signi®cant dierences in isometric MVC force of plantar¯exor muscles relative to body mass were found among the pre-and post-pubertal boys and men. These ®ndings were consistent with several other studies (Seger and Thorstensson 1994;Housh et al 1996) the results of which have indicated that age-related increases in voluntary muscle strength are not accounted for by changes in body mass. The studies which have used anthropometric indices (Davies et al 1983) or ultrasonic techniques (Ikai and Fukunaga 1968) have reported that isometric strength expressed per unit of muscle crosssectional area (CSA) of plantar¯exor and elbow¯exor muscles would appear to remain unchanged throughout adolescence and early adulthood.…”
Section: Discussionsupporting
confidence: 92%
“…However, it has been suggested that for knee extensor muscles the ability to produce strength proportional to muscle CSA is lower in children compared with young adults (Kanehisa et al 1994(Kanehisa et al , 1995a. It has been hypothesized that the increases in muscle mass per unit of fat free mass, neural maturation, or both, contribute to the increase in strength across age (Weir et al 1992;Housh et al 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, the present study consid- ered variables which were absolute (PT) and relative (CHQ, FHQ and leg symmetry) as well as pubertal and chronological age. The fi ndings for PT across age group in all conditions were in agreement with previous authors in that as age increases, so does PT [2,9,10,12,16,28] . However, novel fi ndings in the present study illustrated specifi c relationships between ageing and various muscle actions and modes of contraction.…”
Section: Discussionsupporting
confidence: 91%
“…However, as exposure to training and game play increases with progression through age groups, information regarding the impact of this dominance eff ect is unknown. Inclusion of pubertal development staging may also give insight into the eff ects on thigh muscle balance and absolute PT, which has not been reported in previous studies of cross sectional design [2,9,12,16,28] . Investigation of this type may lead to conclusions regarding the eff ect of age and pubertal development on these variables, which may in turn lead to age specifi city in injury prevention, training and rehabilitation techniques.…”
Section: Introductionmentioning
confidence: 95%